Volume 1: Symposia, Parts a and B 2006
DOI: 10.1115/fedsm2006-98042
|View full text |Cite
|
Sign up to set email alerts
|

IceCube CFD Drilling Model

Abstract: A numerical model of a hot water drill used to produce deep holes in clear ice at the South Pole for the IceCube neutrino observatory program scheduled for completion in 2010 has been developed. The model was built using the ANSYS commercial computational fluid dynamics (CFD) code, ANSYS CFX. This drill model is helping us to understand the water/ice melting process near the bottom of the drill hole, and to evaluate the influence of nozzle size, spray angle, water flow rate, and water temperature on the drill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Martin et al . [] presented the results of a modeling study of hot water drilling that was developed to optimize drilling performance in the multi‐hole drilling program in connection with the IceCube neutrino observatory at the South Pole. This project involved the drilling of 0.5 m diameter holes to a depth of 1300 m in ice at −40°C.…”
Section: Forced Convective Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Martin et al . [] presented the results of a modeling study of hot water drilling that was developed to optimize drilling performance in the multi‐hole drilling program in connection with the IceCube neutrino observatory at the South Pole. This project involved the drilling of 0.5 m diameter holes to a depth of 1300 m in ice at −40°C.…”
Section: Forced Convective Heat Transfermentioning
confidence: 99%
“…Local heat transfer coefficients are then calculated from local water velocity and temperature. Martin et al [] showed wide variations in heat transfer coefficient between the center and the periphery of the hole, thus demonstrating that simple models based on an average heat transfer coefficient are unlikely to be useful.…”
Section: Forced Convective Heat Transfermentioning
confidence: 99%
“…Current research on ARGs largely attends to actual game play and player participation [4,10,11,14]. While these studies draw upon the design process of the ARG to inform their analyses, design discussions are incidental, not central.…”
mentioning
confidence: 99%
“…While these studies draw upon the design process of the ARG to inform their analyses, design discussions are incidental, not central. Few have converged specifically on the design processes involved, the interdisciplinary skills required for successful design, or the ways in which designers might scaffold student learning [10].…”
mentioning
confidence: 99%